Antacid Use and De Novo Brain Metastases in Patients with Epidermal Growth Factor Receptor-Mutant Non-Small Cell Lung Cancer Who Were Treated Using First-Line First-Generation Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors - Chen, Yu-Mu; Lai, Chien-Hao; Chang, Huang-Chih; Chao, Tung-Ying; Tseng, Chia-Cheng; Fang, Wen-Feng; Wang, Chin-Chou; Chung, Yu-Hsiu; Wang, Yi-Hsi; Su, Mao-Chang; Liu, Shih-Feng; Huang, Kuo-Tung; et al. (PloS one, 2016)
Antacid treatments decrease the serum concentrations of first-generation epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs), although it is unknown whether antacids affect clinical outcomes. As cerebrospinal fluid concentrations of TKIs are much lower than serum concentrations, we hypothesized that this drug-drug interaction might affect the prognosis of patients with de novo brain metastases. This retrospective study evaluated 269 patients with EGFR-mutant non-small cell lung cancer (NSCLC) who had been diagnosed between December 2010 and December 2013, and had been treated using first-line first-generation EGFR-TKIs. Among these patients, we identified patients who concurrently used H2 receptor antagonists (H2RAs) and proton pump inhibitors (PPIs) as antacids. Patients who exhibited >30% overlap between the use of TKIs and antacids were considered antacid users. Fifty-seven patients (57/269, 21.2%) were antacid users, and antacid use did not significantly affect progression-free survival (PFS; no antacids: 11.2 months, H2RAs: 9.4 months, PPIs: 6.7 months; p = 0.234). However, antacid use significantly reduced overall survival (OS; no antacids: 25.0 months, H2RAs: 15.5 months, PPIs: 11.3 months; p = 0.002). Antacid use did not affect PFS for various metastasis sites, although antacid users with de novo brain metastases exhibited significantly shorter OS, compared to non-users (11.8 vs. 16.3 months, respectively; p = 0.041). Antacid use did not significantly affect OS in patients with bone, liver, or pleural metastases. Antacid use reduced OS among patients with EGFR-mutant NSCLC who were treated using first-line first-generation EGFR-TKIs, and especially among patients with de novo brain metastases.